만성폐쇄성폐질환 외래환자에서 자기효능감증진 호흡재활프로그램의 효과 - 장희정; Jang Hee Jung; 김정엽; Jung Youp Kim (Tuberculosis and respiratory diseases, 2006)
배경: 만성폐쇄성폐질환의 여러 가지 호흡재활프로그램 중에서 자기효능감을 증진시키는 것이 호흡재활치료에 효과적이라는 국외 보고는 있으나 국내에서는 연구가 시도되지 않았다. 저자들은 만성폐쇄성폐질환자에서 자기효능감증진 호흡재활프로그램의 효과를 알아보기 위하여 이 연구를 하였다. 대상 및 방법: 대상은 호흡기내과 외래에서 진료 받는 만성폐쇄성폐질환자 중 GOLD분류에 의한 Ⅱ, Ⅲ 병기 환자로 하였으며, 치료군 18명, 대조군 18명으로 선정, 비교하였다. 연구는 무작위할당 대조군 전-후연구로 이루어졌다. 저자들이 개발한 자기효능감증진 호흡재활프로그램을 8주 동안 실시하였으며 치료군은 실시 전, 4주, 8주째는 1:1의 교육과 상담이 이루어졌고 전화상담은 매주 1~2회 이루어졌다. 교육과 상담으로 대리경험, 성취경험 등이 이루어지도록 하였고 매일 가정에서 운동훈련과 이완요법을 수행하도록 하여 성취경험과 정서적 이완이 이루어지도록 하였다. 대조군은 프로그램 실시 전에 1:1의 교육과 상담만 제공하였다. 평가는 자기효능감, 평소 호흡곤란, 운동유발호흡곤란, 운동내구성은 6분 걷기 거리로, 폐기능, 삶의 질 등을 양 군에서 측정 비교하였다. 결과: 자기효능감증진 호흡재활프로그램은 대조군보다 치료군에서 유의하게 자기효능감이 향상되었다. 평상 시 호흡곤란, 운동 시 호흡곤란, 6분 걷기 거리도 치료군에서 유의하게 향상되었다. 그러나 폐기능은 유의한 차이가 없었다. 자기효능감증진 호흡재활프로그램은 치료군에서 삶의 질도 유의하게 향상되었다. 결론: 만성폐쇄성폐질환자에서 자기효능감증진 호흡재활프로그램은 자기효능감, 운동내구성, 삶의 질을 증가시키고 운동유발 호흡곤란 정도를 감소시키는 효과가 있었으며, 자기효능감증진 호흡재활프로그램은 만성폐쇄성폐질환자의 호흡재활치료로 효과적으로 활용될 수 있겠다. Background: The aim of this study was to determine the effectiveness of self-efficacy promoting pulmonary rehabilitation in patients with chronic obstructive pulmonary disease (COPD). Methods: thirty six patients, with clinically stable COPD were randomly assigned: 18 to a rehabilitation group and another 18 as a control group, The subjects participated in a the self-efficacy promoting pulmonary rehabilitation program for 8 weeks. This program consisted of education, breathing retraining, exercise training, relaxation and counseling. The control group received education only. The outcome variables were self-efficacy, dyspnea, exercise endurance, pulmonary function, and quality of life. Dyspnea was measured using the modified Borg scale. Exercise endurance was measured by the six minute walking distance. The quality of life was measured by the quality of life index for pulmonary disease patients. Results: In the rehabilitation group after performing the self-efficacy promoting pulmonary rehabilitation program, the self-efficacy score, exercise endurance, and quality of life score were higher than the control group (p=0.007, p=0.038, and p=0.039, respectively). and the exertional dyspnea score was significantly lower than controls(p=0.045). However, the dyspnea score and FEV1 were similar after performing the self-efficacy promoting pulmonary rehabilitation program. Conclusion: The self-efficacy promoting pulmonary rehabilitation program is effective to in improve self-efficacy, exertional dyspnea, exercise endurance and quality of life in patients with COPD. (Tuberc Respir Dis 2006; 61: 533-546)